The Models of North Sumatra Provincial Government Policy in Resolving the Ex-Hgu Land Conflicts of PTPN II Plantations in Deli Serdang Regency - Isnaini Isnaini; Rizkan Zulyadi; Abdul Kadir (Budapest International Research and Critics University, 2020)
This study is to find an alternative model of North Sumatra provincial government policy in resolving the ex-hgu land conflicts of PTPN II plantations in Deli Serdang Regency. This study is based on the fact that regional autonomy as regulated in Law Number 23 of 2014 gives the authority to the regional government in autonomy to resolve disputes over arable land in their territories. One of them relates to ex-HGU PTPN II land disputes starting in 2002 with the Central BPN Decree number 42, 43 and 44 / HGU / BPN / 2002 and Decree Number 10/2004 regarding the granting of an extension of the term of the Right to Cultivate (HGU) covering an area of 5,873 , 068 Ha from PTPN II HGU. However, the problem arises because of legal uncertainty over the distribution of land that had expired during the PTPNII HGU, so that horizontal or vertical conflicts (community cultivators, PTPN II, government and developers) occurred. From the results of the study, it was concluded that first, the ineffective model of handling policies that are appropriate, fast, and comprehensive is carried out by the government. This relates to the problem of land conversion where there is a lack of orderly administration and past land data. So that each party has its own claim on land ownership and ownership. Both the boundary and location of land parcels. Second, legal uncertainty, that there are legislation that overlaps both horizontally and vertically as well as regulated substance